COST OPTMIZATION WITH INTERNET SUPPORTED FMEA AND FUZZY FMEA ANALYSIS - Buket Karatop; Ceren Arslan Kazan; Halil Koruca (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The global competitive environment forces businesses to produce high-quality and low-cost products and they develop strategies in this regard. At the same, production risks should be identified and their effects on quality and cost should be minimized. The FMEA method is a risk analysis method that produces effective results. Traditional FMEA and Fuzzy FMEA analyses were conducted in the machining workshop of an enterprise with a wide range of products and semi-products in this study. Real-time data was obtained with the help of an embedded set of data processing cards, which use IoT technology. These data have been used to identify errors that cause production bottlenecks, and they were obtained without relying on the machine operator. Improvements were made in the riskiest subjects during the three-month analysis, and it was discovered in the cost records that a total reduction of 6% in production costs was achieved. Simultaneously, traditional FMEA and fuzzy FMEA results were compared.